Ter,Pe Peningkatan Skill Short Passing Sepakbola Pemain SSB Sarilamak United U12 - Normandi Alpha Junio; Sari Mariati; John Arwandi; M Ridwan (Performa, 2021)
This study’s main issue was lack of short passing skill for Sarilamak United Soccer School player U12. The aim of this study was to examine the effect of exercise models toward of soccer short passing skill increased for Sarilamak United Soccer School player U12. Type of this research was quasi experiment with one group pretest-posttest design. The population for this study were 63 player. All of twelve sample was determined by purposive sampling technique. The short pass test was an instrument test for this study with t-test data analysis technique. The Hypotesis test discovered that Ho declined and Ha accepted. Where tcount (4,72) was higher than ttable (2,20). The result of average comparison between pre-test (102,1) and post-test (110,3) indicated that exercise models were able to gave an improvement about 7,44%. In summary, there was a significant effect from giving the exercise models toward of soccer short passing skill increased for Sarilamak United Soccer School player U12.